2000
DOI: 10.1177/104063870001200608
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Susceptibility of Porcine Respiratory Pathogens to Tilmicosin

Abstract: Bacterial isolates obtained from swine with various clinical diseases were tested for susceptibility to tilmicosin by minimum inhibitory concentration (MIC) and Kirby-Bauer disk diffusion tests using National Committee on Clinical Laboratory Standards methodology. The tilmicosin MIC90 was < or =0.125 microg/ml for Erysiopelothrix rhusiopathiae, < or = 1 microg/ml for Haemophilus parasuis isolates, 8 microg/ml for Actinobacillus suis and Pasteurella multocida type A, 16 microg/ml for toxigenic and nontoxigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 9 publications
2
19
0
Order By: Relevance
“…However, three studies from the United States (2,3,11) were suitable for comparisons with our data. In the first study (11), the range of MICs as well as the MIC 90 s of various antimicrobial agents were determined in 1988 for 48 porcine B. bronchiseptica isolates collected in the United States.…”
mentioning
confidence: 97%
“…However, three studies from the United States (2,3,11) were suitable for comparisons with our data. In the first study (11), the range of MICs as well as the MIC 90 s of various antimicrobial agents were determined in 1988 for 48 porcine B. bronchiseptica isolates collected in the United States.…”
mentioning
confidence: 97%
“…Pharmacokinetics of tilmicosin after intravenous administration were limited and unsuccessful due to its considerable cardiovascular adverse effects and deaths ( In the present study, mean peak plasma concentration (1.25±0.09 μg/mL) of tilmicosin phosphate (tilmicoral ® ) is higher than MICs for Ornithobacterium rhinotracheale (0.06-1 μg/mL) (Varga et al 2001) and Mycoplasma synoviae and MG (0.0125-0.1 μg/mL) and lower than the MICs for Clostridium perfringens strains isolated from commercial broiler farms (Watkins et al 1997) and Actinobacillus suis and Pasteurella multocida isolated clinically from swine (DeRosa et al 2000). This clearly demonstrates that administration of tilmicosin at the recommended dosage is effective for control of respiratory disease in several animal species (Moore et al 1996, Christodoulopoulos et al 2002 due to its prolonged stay in lung tissues at therapeutic concentrations (Papich & Riviere 2001).…”
Section: Discussionmentioning
confidence: 90%
“…Tilmicosin is a new semi-synthetic macrolide antibiotic developed from tylosin with potent immune-modulation and anti-inflammatory effects (Buret, 2010;Cao et al, 2006;Ci et al, 2011). Tilmicosin has been developed for veterinary use as a premix feed formulation for swine and is considered efficacious against several porcine respiratory pathogens (DeRosa et al, 2000;Fittipaldi et al, 2005;Shryock et al, 2002;Thacker et al, 2001). Recently, Du et al (2011) showed that tilmicosin exhibited strong antiviral effects on PRRSV replication in cultured porcine alveolar macrophages in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Tilmicosin is a new semi-synthetic macrolide antibiotic derived from tylosin B (Scorneaux & Shryock, 1998) and is an effective antimicrobial for Gram-positive and some Gram-negative bacteria (Brumbaugh et al, 2002;DeRosa, Veenhuizen, Bade, & Shryock, 2000;Fittipaldi et al, 2005;Shryock, Staples, & DeRosa, 2002;Thacker, Young, Erickson, & DeBey, 2001). A recent study showed that tilmicosin exhibited strong antiviral effects on PRRSV replication in cultured porcine alveolar macrophages in a dose-dependent manner (Du et al, 2011).…”
Section: Introductionmentioning
confidence: 99%